(untitled) (Conferencea, 2022)
Nowadays technology, information and knowledge explosion have led to the increase of teaching and learning English as an international language. Teaching and learning English in different countries have been faced with some problems. English has been taught in schools in Uzbekistan since some years ago. The organizing the learning method is to meet a specific educational goal. Programmed teaching, lectures, and practical display are considered as examples of teaching methods.